Pengukuran Tak Langsung pada Proses Kerja Eksisting dan Perbaikan Produksi Tempe dengan Metode Maynard Operation Sequence Technique - Nia Yunita Listianingrum; Amalia Amalia; Arokib Darjat Saputra; Felix Christian Santoso (Program Studi Teknik Industri Universitas Setia Budi, 2024)
Time measurement is carried out to determine the length of time required for workers to complete the production process, starting from raw materials to finished goods. Due to the low production volumes, the Barokah Tegal Tempe Home Industry's tempeh production process is not producing optimal results, which prevents them from fulfilling customers’ demands. Limited production capabilities due to lengthy processing times. Extended processing durations may result from non-value-adding movements or activities, as well as manual labor techniques. The aim of this research is to examine the tempe production process, with a focus on the three primary work stations—the peeling, washing, and mixing operations. The method used is the Maynard Operation Sequence Technique (MOST), where measurements are carried out on existing conditions and proposed work improvements. The research results show that the existing time measurement in the peeling process is 104,840 Time Measure Units (TMU), washing 316,020 TMU, and mixing 127,360 TMU. In order to reduce processing time, work tools should be able to do away with pointless movements. The proposed work improvement time for peeling process is 60,680 TMU, washing 93,800 TMU, and mixing 50,300 TMU. Calculations of the existing condition and proposed improvement can result in a 62% increase in working time efficiency.